Development, characterization and optimization of biopolymers films based on starch and flour from jabuticaba (Myrciaria cauliflora) peel. (1st May 2021) - Ribeiro Sanches, Marcio Augusto; Camelo-Silva, Callebe; Tussolini, Loyse; Tussolini, Martha; Zambiazi, Rui Carlos; Becker Pertuzatti, Paula
Highlights: Biodegradable films were prepared with jaboticaba peel flour and corn starch. The increase of glycerol content decreased mechanical and barrier properties. The content increase of jabuticaba and glycerol made the films more hydrophilic. The selected formulation showed the best mechanical and barrier properties. Jabuticaba flour increased the thickness and decreased the solubility of films. Abstract: In this study, the influence of the concentration of flour from jabuticaba peel (FJP) and the concentration of glycerol (CG) on the physicochemical, barrier, mechanical, optical, spectroscopic and biodegradability properties of corn starch films was evaluated using response surface methodology. The increase in the concentrations of FJP and CG enhanced the thickness and permeability to water vapor, and made the films more hydrophilic. In addition to that, the interaction between the two variables caused reduction in the solubility of the films. High concentrations of FJP and CG reduced the maximum tensile strength, and increased CG increased the elongation and decreased the young's modulus of the films. Among the tests studied, the T1 film (15.80% FJP and 15.80% CG) was biodegradable, presenting the best mechanical and barrier properties such as low water vapor permeability, solubility and water holding capacity, showing great potential to be used as biodegradable packaging system.